ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS DAN RENTABILITAS PADA PT.BANK NEGARA INDONESIA (PERSERO), TBK PERIODE 2019-2023 - Febrianto P, Michael; Silaban, Adanan; Hutapea, Herti Diana (JURNAL LENTERA AKUNTANSI, 2024)
This study aims to determine the financial performance of PT. Bank Negara Indonesia (Persero), Tbk for the period 2019-2023 in terms of liquidity and profitability ratios. The liquidity ratio is proxied by the Cash Ratio, Loan to Deposit Ratio, Loan to Asset Ratio, Banking Ratio and Profitability is proxied by Net Profit Margin, Return on Equity, Return on Asset Ratio, Return on Investment Ratio, Interest Expense Ratio. The technique used by the author to complete this research is the documentation technique and data analysis of BNI's financial reports that can be accessed via the internet media including the financial reports of PT. Bank Negara Indonesia (Persero), Tbk for the 2019-2023 period. The data used is secondary data collected using the documentation method. The data analysis technique used in qualitative research is comparative ratio analysis. The test results are liquidity ratios such as Cash Ratio in 2019-2023 meet BI standards, LDR in 2019-2020 is in a healthy state, the highest Loan to Asset Ratio occurred in 2019 at 69.39% and BNI's financial performance is in a healthy state. The highest Banking Ratio occurred in 2019 at 95.58%. Profitability is measured from NPM in 2019 of 142.11%, in 2022 of 123.11% and in 2023 of 130.09% in a healthy state, In 2023 BNI's ROE is in a healthy state, BNI's highest Return on Asset (ROA) occurred in 2023 of 2.36% in a healthy state. BNI's highest Return on Investment (ROI) occurred in 2023 of 1.94% and is in a healthy state. BNI's highest Interest Expense Ratio occurred in 2019 of 9.35% in a healthy state.